Effects of fungicides, bioagents and botanicals against the post harvest diseases of mandarin orange - K.S. RAGHUWANSHI, P.J. MAHAJAN*and (Indian Phytopathology, 2016)
Post harvest losses of Mandarin Orange (Citrus reticulata Balance) is to the tune of 34.30% which is caused by various biotic agents. To know the causes and remidies of the various post harvest losses of the mandarin orange, the infected fruit were collected from the market and separated the fungi associated with the infected fruit viz;Aspergillus niger, Penicillium digitatum and Rhizopus stolonifer and pathogenecity of all three isolates were proved. The pathogen Aspergillus niger produced brown to black lesions on fruits. Penicilliumdigitatum produced greenish spots on fruits. Rhizopus stolonifer produced blackening thereafter inducing severe rotting. In chemical control study, Potassium metabisulphide, Hexaconazole and Propiconazole were most effective against Apergillus niger. Hexaconazole was remained most effective against Penicilliumdigitatum as well, while Copper oxychloride, P. metabisulphide, Hexaconazole, Propiconazole, Propenophos were effective against Rhizopus stolonifer. Hexaconazole was effective against all pathogens. In the study on effects of bioagents, Trichoderma harzianum significantly suppressed the growth of Penicillium, Aspergillus while others were not effective. 10% concentration of all herbal extracts except Aloe vera was effective against all three pathogens.